HBeAg Is Indispensable for Inducing Liver Sinusoidal Endothelial Cell Activation by Hepatitis B Virus - Xie, Xiaohong; Luo, Jinzhuo; Zhu, Dan; Zhou, Wenqing; Yang, Xuecheng; Feng, Xuemei; Lu, Mengji; Zheng, Xin; Dittmer, Ulf; Yang, Dongliang; Liu, Jia (Frontiers in Cellular and Infection Microbiology, 2022)
Background and Aims Liver sinusoidal endothelial cells (LSECs) serve as sentinel cells to detect microbial infection and actively contribute to regulating immune responses for surveillance against intrahepatic pathogens. We recently reported that hepatitis B e antigen (HBeAg) stimulation could induce LSEC maturation and abrogate LSEC-mediated T cell suppression in a TNF-α and IL27 dependent manner. However, it remains unclear how HBeAg deficiency during HBV infection influences LSEC immunoregulation function and intrahepatic HBV-specific CD8 T cell responses. Methods The function of LSECs in regulating effector T cell response, intrahepatic HBV-specific CD8 T cell responses and HBV viremia were characterized in both HBeAg-deficient and -competent HBV hydrodynamic injection (HDI) mouse models. Results LSECs isolated from HBeAg-deficient HBV HDI mice showed a reduced capacity to promote T cell immunity in vitro compared with those isolated from wild-type HBV HDI mice. HBeAg expression replenishment in HBeAg-deficient HBV HDI mice restored the HBV-induced LSEC maturation, and resulted in potent intrahepatic anti-HBV CD8 T cell responses and efficient control of HBV replication. Moreover, in vivo TNF-α, but not IL27 blockade in HBV HDI mice impaired HBV-specific CD8 T cell immunity and delayed HBV clearance. Conclusion Our study underlines that HBeAg is indispensable for HBV-induced LSEC maturation to trigger intrahepatic HBV-specific T cell activation, and provides a new mechanism to elucidate the intrahepatic immune microenvironment regulation upon HBV exposure.